2011
DOI: 10.1140/epjp/i2011-11019-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell motility: A viscous fingering analysis of active gels

Abstract: Abstract. The symmetry breaking of the actin network from radial to longitudinal symmetry has been identified as the major mechanism for keratocytes (fish cells) motility on solid substrate. For strong friction coefficient, the two dimensional actin flow which includes the polymerisation at the edge and depolymerisation in the bulk can be modelled as a Darcy flow, the cell shape and dynamics being then modelled by standard complex analysis methods. We use the theory of active gels to describe the orientational… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…[12], it was found that actomyosin fragments do exhibit a viscous-fingering-like morphological instability, but the fundamental question of whether such a model contains the minimal ingredients to initiate and sustain motion remained unsolved. Extensions of this model to include an explicit symmetry-breaking of the dynamic equations to generate motility have also been reported [16]. Here we show that spontaneous symmetry breaking of the circular shape is sufficient to initiate and sustain motion, even in the absence of myosin motors and largescale polarization, when nonlinearities are taken into account.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…[12], it was found that actomyosin fragments do exhibit a viscous-fingering-like morphological instability, but the fundamental question of whether such a model contains the minimal ingredients to initiate and sustain motion remained unsolved. Extensions of this model to include an explicit symmetry-breaking of the dynamic equations to generate motility have also been reported [16]. Here we show that spontaneous symmetry breaking of the circular shape is sufficient to initiate and sustain motion, even in the absence of myosin motors and largescale polarization, when nonlinearities are taken into account.…”
supporting
confidence: 53%
“…However, the mode m ¼ 1 must be exactly marginal, ð1Þ ¼ 0, reflecting the translational invariance of the problem. Explicit symmetry breaking of the equations has been discussed as a possible mechanism to generate motion [16]. Here, we are interested in whether spontaneous symmetry breaking via a morphological instability is by itself sufficient to initiate and sustain motion, a fundamental question that must be addressed at the nonlinear level.…”
mentioning
confidence: 99%
“…The latter is continuously supplied by an incoming flux from the third dimension normal to the epithelial layer and uptaken by cell receptors. As shown in [18], the thinness of the moving layer transforms the threedimensional process into a two-dimensional model, where the localized thickness variation at the border contributes to a tension T. In addition, we assume that a strong viscous friction exists between the moving layer and the substrate [19][20][21][22][23], which allows writing a Darcy's law for the average velocity field inside the tissue, while cell-cell interactions and mitosis are transformed into interface boundary conditions in the sharp interface limit. We first present the physical model, then the analytical treatment giving an explicit solution for the circular geometry and a study of its stability.…”
Section: Introductionmentioning
confidence: 99%
“…A multicomponent theory based on irreversible thermodynamics is derived in [2,9,10]. The theory seems to be able to make a number of successful predictions, e.g., the onset of spontaneous flow [11,12], motility and spontaneous division of active nematic droplets [13][14][15].…”
Section: Introductionmentioning
confidence: 99%